A deterministic contact evolution and scuffing failure analysis considering lubrication deterioration due to temperature rise under heavy loads. (May 2021) - Lyu, Bugao; Meng, Xianghui; Zhang, Rui; Wen, Chengwei
Highlights: A new 3D transient deterministic mixed-TEHL model is established. A detailed contact evolution analysis resulting in scuffing failure is conducted. The role that the thermal effect plays in scuffing mechanism is revealed. Abstract: Nowadays many friction pairs in engineering inevitably work under mixed lubrication regime, during which both hydrodynamic lubrication and asperities contact share the heavy loads. The heat generated by friction, especially by asperities contact friction, will deteriorate the lubrication performance, and then a scuffing failure may happen. In this study, based on a deterministic mixed thermal elastohydrodynamic lubrication (TEHL) model, the lubrication deterioration, the related temperature rise, and the contact evolution are analyzed together. The simulation results show that under a light load, the temperature of the lubricant film initially increases, but it quickly stabilizes to a not too high value. However, under a heavy load, a much higher temperature rise has happened. Meanwhile the lubrication performance is seriously deteriorated, and the contact ratio increases sharply. It indicates that the contact evolution may lead to lubricant film breakdown and successively surface scuffing under heavy loads.